2020
DOI: 10.1111/jbi.13817
|View full text |Cite
|
Sign up to set email alerts
|

Chemical variations in Quercus pollen as a tool for taxonomic identification: Implications for long‐term ecological and biogeographical research

Abstract: Aim: Fossil pollen is an important tool for understanding biogeographical patterns in the past, but the taxonomic resolution of the fossil-pollen record may be limited to genus or even family level. Chemical analysis of pollen grains has the potential to increase the taxonomic resolution of pollen analysis, but present-day chemical variability is poorly understood. This study aims to investigate whether a phylogenetic signal is present in the chemical variations of Quercus L. pollen and to assess the prospects… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 66 publications
0
14
1
Order By: Relevance
“…Both experimental (Coffey, Prinsen, Jansen, & Conway, 2017) and field evidence (Martz et al, 2007;Solanki et al, 2019) indicate that plants can screen UV radiation more effectively under low temperatures, and that the accumulation of UV-B-absorbing compounds in plant-leaf tissue can sometimes be the result of interactive effects with temperature at high elevations and latitudes (Neale et al, 2021). For example, Martz et al (2007) assessed the variations in both the concentration and composition of UV-B-absorbing compounds in Pinus sylvestris needles using UV-exclusion field chambers in Finland, and found UV-A/B exclusion had a significant effect on five out of 46 soluble phenolic compounds within the leaf needles. However, they also showed that the the effects of UV-B radiation on pigments, related to protection against light-induced oxidative stress, were only detectable under freezing temperatures and high solar irradiance in the spring.…”
Section: Variations In the Accumulation Of Uv-b Absorbing Compounds At The Population Levelmentioning
confidence: 99%
“…Both experimental (Coffey, Prinsen, Jansen, & Conway, 2017) and field evidence (Martz et al, 2007;Solanki et al, 2019) indicate that plants can screen UV radiation more effectively under low temperatures, and that the accumulation of UV-B-absorbing compounds in plant-leaf tissue can sometimes be the result of interactive effects with temperature at high elevations and latitudes (Neale et al, 2021). For example, Martz et al (2007) assessed the variations in both the concentration and composition of UV-B-absorbing compounds in Pinus sylvestris needles using UV-exclusion field chambers in Finland, and found UV-A/B exclusion had a significant effect on five out of 46 soluble phenolic compounds within the leaf needles. However, they also showed that the the effects of UV-B radiation on pigments, related to protection against light-induced oxidative stress, were only detectable under freezing temperatures and high solar irradiance in the spring.…”
Section: Variations In the Accumulation Of Uv-b Absorbing Compounds At The Population Levelmentioning
confidence: 99%
“…The bands at ~1100 cm-1 are due to C-O of alcohol group in CA and JO. The band at 852 cm-1 of CA extract refers to the presence of aromatic groups [32] of sporopollenin.…”
Section: Antioxidant Potential and Functionality Of The Pollen Extractsmentioning
confidence: 99%
“…Our work addresses a major gap in paleo-vegetation studies that typically rely on palinological data, which tend to fail in delimitating the distribution of tree species accurately, particularly in the case of deciduous oaks (Sect. Quercus ) 17 , 18 . Our study suggests that conservation efforts should target Q. canariensis and Q. estremadurensis because both taxa presently show a scattered (known and projected) distribution.…”
Section: Discussionmentioning
confidence: 99%
“…We currently ignore the biogeographic trajectories that co-occurring oak species inhabiting this ecotone experienced in response to climate changes during the Late Quaternary. This is partly because most studies aimed to delineate past distributional ranges are based on fossil pollen records that provide a broad depiction of plant communities but fail to distinguish between deciduous oak species 17 , 18 . Recent approaches based on species distribution modeling (SDM) can provide new insights to advance our understanding of the biogeographic past trajectories 19 21 .…”
Section: Introductionmentioning
confidence: 99%